Transformational Leadership, Green Human Resource Management dan Job Embeddedness: Apakah cukup untuk menekan Quitting Intention karyawan generasi Z? - Dewa Dharmanegara Kesumadiputra; Intan Novela Qurrotul Aini (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of transformational leadership and green human resource management on quitting intention among Generation Z hotel employees in Yogyakarta, with job embeddedness as a mediating variable. Using a quantitative cross-sectional design, data were collected from 204 respondents and analyzed using PLS-SEM with SmartPLS 3. The findings indicate that transformational leadership significantly enhances job embeddedness, whereas green human resource management does not significantly affect job embeddedness or quitting intention. Job embeddedness also fails to reduce quitting intention. These results suggest that Generation Z retention strategies should emphasize career development, flexibility, and supportive leadership beyond sustainability practices.